Middle Miocene (Serravallian) wetland development on the northwest edge of Europe based on palynological analysis of the uppermost Brassington Formation of Derbyshire, United Kingdom - McCoy, Jessica; Barrass-Barker, Tabitha; Hocking, Emma; O'Keefe, Jennifer M.K.; Riding, James B.; Pound, Matthew (Palaeogeography, Palaeoclimatology, Palaeoecology, 2022)
In this paper, we describe palynological assemblages in the Middle Miocene (Serravallian) Kenslow Member of the Brassington Formation at Bees Nest Pit, near Brassington, Derbyshire, U.K., and infer vegetation types and their palaeoclimate implications. The limited lateral extent of the 1.33 m-thick succession of clay and lignite, and its position surrounding fragments of a large tree trunk, suggests that the succession may have accumulated within a tree throw hole or possibly within a shallow stagnant pond, although aquatic lacustrine palynomorphs have not been identified to confirm this latter hypothesis. The stratigraphical distribution of palynological assemblages, based on 58 samples allows reconstruction of a wetland succession. Two pollen zones were identified using CONISS cluster analysis, and a predominantly warm-temperate and mixed mesophytic forest biome was recognised with Tsuga conifer pollen-types being dominant (<42%) in both pollen zones. Changes in the make-up of this forested wetland were in response to local environmental changes rather than major climatic shifts. Wetland development culminated in the formation of a relatively open shrub and reed-dominated mire which produced the lignite-precursor peat. Applying the Co-existence Approach, Mean Annual Temperature was 15.6–21.7 °C and Mean Annual Precipitation was 703–1682 mm indicating a warm-temperate to subtropical palaeoclimate, and both parameters show no significant change through the section. Findings suggest that, following the Middle Miocene Climatic Optimum, the Serravallian climate of the northwestern margin of Europe remained much wetter than Central Europe, where more arid climates have been reconstructed, and this difference may have been due to the influence of the proto-North Atlantic Current.